An Unusual Cause of Dysphagia: A Large Expectorated Arteriovenous Malformation - Griffin, Aaron S. (Ochsner J, 2015)
BACKGROUND: Vascular malformations are generally detected in childhood or adolescence with first presentations in adulthood being rare. CASE REPORT: We report the case of a 52-year-old female with threatened compromise of her airway after expectorating a massive arteriovenous malformation anchored at the supraglottis. The only preceding symptom was dysphagia. The lesion was resected, the patient had a quick recovery, and she has shown no evidence of recurrence. CONCLUSION: Although uncommon, vascular malformations of the supraglottis or hypopharynx should be considered in the differential diagnosis of a patient presenting with dysphagia because of the potential to cause disastrous airway compromise. Although a lesion presenting acutely mandates a definitive airway plan, when clinically possible, computed tomography scan and indirect laryngoscopy can provide useful information for the airway and operative teams.